On Bifurcation of Noether Points in Discrete Spectrum of Linear Operators - Rakhimov, Davran Ganiyevich (Eurasian Mathematical Journal, 2015)
In this work in the development of our previous articles [3, 4] the perturbation of the Noether points in discrete spectrum of linear operator-functions is considered. With the help of the perturbed operator regularization an approach is suggested allowing to reduce the problem of its eigenvalues determination (which can turn out to be multiple) to simple ones together with correspondent eigenelements.